Post-Translational Modifications of Histones in Vertebrate Neurogenesis - Mitrousis, Nikolaos; Tropepe, Vincent; Hermanson, Ola (Frontiers in Neuroscience, 2015)
The process of neurogenesis, through which the entire nervous system of an organism is formed, has attracted immense scientific attention for decades. How can a single neural stem cell give rise to astrocytes, oligodendrocytes and neurons? Furthermore, how is a neuron led to choose between the hundreds of different neuronal subtypes that the vertebrate CNS contains? Traditionally, niche signals and transcription factors have been on the spotlight. Recent research is increasingly demonstrating that the answer may partially lie in epigenetic regulation of gene expression. In this article, we comprehensively review the role of posttranslational histone modifications in neurogenesis in both the embryonic and adult CNS.